Impact of the COVID-19 pandemic on population-based cancer screening, a nationwide retrospective study in Taiwan - Chih-Hsuan Su; Pi-Shan Hsu; Chu-Sheng Lin (BMC Health Services Research, 2023)
Abstract Background The Coronavirus disease 2019 (COVID-19) pandemic has placed a great burden on Taiwan’s health care system. It has also had a great impact on other public health issues, including cancer screening. Delayed cancer screening was also noticed in the U.S. during the pandemic, which may have led to both delayed diagnosis and poor prognosis. In Taiwan, population-based cancer screening for breast cancer, oral cancer, colon cancer and cervical cancer has been executed and ongoing for years. Method In this study we have analyzed the change in screening numbers for cancer during the period of the 2019 to 2021 COVID-19 outbreak in Taiwan. Results Through our results we found that total cancer screening numbers decreased from 307,547 to 103,289 (a 66% decrease) from the years 2020 to 2021. Specifically, a 63%, 79%, 65% and 71% decrease in screening cases was seen for colon cancer, oral cancer, cervical cancer and breast cancer, respectively, during that period. A similar condition was noticed when comparing 2019 to 2021 when the disclosed total cancer screening numbers decreased by 70% (2019–2021); 65%, 83%, 70% and 76% in colon cancer, oral cancer, cervical cancer and breast cancer, respectively. Among these various cancer screenings, oral cancer screening showed the greatest reduction rate (a drop of 83% compared to 2019 and 79% compared to 2020). We also compared the reduction rates taken from different regions in Taiwan. It was in Taipei, where most COVID-19 cases were noted, that the greatest reduction rate of cancer screening numbers occurred (a drop of76% compared to 2019 and 74% compared to 2020). A proportional decrease of screening cases was also noticed in all areas when confirmed COVID-19 cases rose. Conclusions Screening for cancers dropped significantly due to the pandemic and its effect on long-term health needs to be evaluated. Additionally, efforts should be taken to address these cancer screening number deficits which have taken place during the COVID-19 pandemic.